THE DARK SIDE OF MOTIVATING PERSONNEL IN CIVIL SERVICE - Yevdokymov, V. (Pressing Problems of Public Administration, 2019)
The notion of motivation is one of the most mythologized notions in the modern literature on management. It is hard to imagine a definition of the notion of motivation, which would clarify and solve all the methodological problems related to the managerial competency. In management, motivation is a process of influencing personnel with the aim of directing and intensifying their activity for the benefit of an organization. Material stimulation is a key form of motivating subordinates. However a manager should understand that a big majority of their subordinates are unwilling to earn more money. They wish only a rise in salary and better living, without making additional efforts. Yet, the results of an organization’s work should not depend on the desire of its personnel to earn more. A discouraging forecast for a superior is as follows: if subordinates have an opportunity to ignore their tasks, they will definitely do it. In this case, a superior should not be offended by this sort of subordinates’ behavior, since they do not do it intentionally, but rather in accordance with the biological laws of survival. A positive forecast is like this: a superior can influence and change a model of their subordinates’ behavior. In order to understand the means which can influence the motivation of subordinates, it is necessary to consider a classification of achievement motives of an individual and their ways to avoid failures. Achievement motivation is a person’s behavioral strategy, oriented to proactive attitude, high results, carrying out diverse activities, seeking approval of management. Avoidance motivation presupposes a different manner of behavior: passivity, fear of failures and making mistakes, a wish to avoid punishment by a superior, evasion of responsibility. Application of avoidance motive is expedient to realize through coercion of a subordinate. It is essential to introduce coercion into operative managerial activity so that a subordinate could understand what negative consequences will be effected by the superior in case of the subordinate’s poor performance. When giving managerial instructions, a leader should clearly explain to a subordinate correct and incorrect ways to carry out actions; in so doing, the leader insures himself/herself against mistakes and inadequacies caused by a subordinate’s incorrect fulfillment of an assignment. If the superior does not specify both the ways, the range of deviations from the expected results can be rather broad, in which case the superior has no manner of right to punish the subordinate. A superior’s placing reliance in subordinates’ “good sense” testifies to his/her low managerial professionalism. Development of professional competency of a leader can be facilitated only by profound knowledge and a continuous learning, persistence in practical implementation of that knowledge, and improvement of managerial skills, which has no boundaries.